Efektivitas pelatihan konselor sebaya dalam meningkatkan keterampilan konseling masalah kesehatan mental pada mahasiswa - Saifan Asadul Haq; Warih Andan Puspitosari (Holistik Jurnal Kesehatan, 2026)
Background: College students are a vulnerable group experiencing mental health issues due to dynamic physical, psychological, and environmental changes. Peer counselors have the potential to be a rapid first-line support, particularly in student living environments (dormitories). Purpose: Evaluation of the effectiveness of peer counselor training in improving counseling skills for mental health–related concerns among peer counselors. Method: A quasi-experimental one-group pretest–posttest design was conducted among 43 Unires students recruited using consecutive sampling. The intervention comprised peer counselor training delivered through theoretical sessions and practical exercises. Counseling skills were measured using a Likert-scale questionnaire that had undergone validity and reliability testing. Pre- and post-training scores were compared using the Wilcoxon signed-rank test. Results: Posttest counseling skill scores were significantly higher than pretest scores (p < 0.05), indicating improved counseling skills following the training. Conclusion: Peer counselor training was effective in improving basic counseling skills related to mental health problems among University Residence students. Integrating structured peer counselor training within university residential programs may strengthen early support for student mental health concerns. Suggestion: The Unires program should be equipped with clear governance (role boundaries, confidentiality SOPs, risk screening, crisis referral pathways), ongoing structured supervision, and regular booster sessions to maintain quality and skill retention; further research should use an experimental design with performance assessment and follow-up to provide more robust and accurate results.   Keywords: Counseling Skills; Mental Health; Peer Counselor; Peer Counseling; Training; University Residence.   Pendahuluan: Mahasiswa berada pada kelompok rentan mengalami masalah kesehatan mental seiring perubahan fisik, psikologis, dan lingkungan yang dinamis. Konselor sebaya berpotensi menjadi dukungan lini pertama yang cepat, khususnya di lingkungan tempat tinggal mahasiswa (asrama). Tujuan: Untuk mengetahui efektivitas pelatihan konselor sebaya dalam meningkatkan keterampilan konseling masalah kesehatan mental. Metode: Penelitian ini menggunakan desain kuasi-eksperimental satu kelompok dengan rancangan pretest–posttest pada 43 mahasiswa University Residence (Unires) di Universitas Muhammadiyah Yogyakarta yang direkrut melalui consecutive sampling. Intervensi berupa pelatihan konselor sebaya yang mencakup sesi teori dan latihan praktik. Keterampilan konseling diukur menggunakan kuesioner skala likert yang telah melalui uji validitas dan reliabilitas. Perbedaan skor sebelum dan sesudah pelatihan dianalisis menggunakan uji Wilcoxon signed-rank. Hasil: Terdapat peningkatan skor keterampilan konseling yang bermakna pada posttest dibandingkan pretest (p < 0.05). Simpulan: Pelatihan konselor sebaya efektif meningkatkan keterampilan konseling dasar terkait masalah kesehatan mental. Pelatihan terstruktur dapat dipertimbangkan sebagai bagian dari program dukungan kesehatan mental di lingkungan asrama. Saran: Program kampus sebaiknya dilengkapi tata kelola yang jelas (batas peran, SOP kerahasiaan, skrining risiko, alur rujukan krisis), supervisi terstruktur berkelanjutan, serta sesi booster berkala untuk menjaga kualitas dan retensi keterampilan; selain itu, penelitian lanjutan perlu menggunakan desain eksperimental dengan penilaian performa dan follow-up agar hasil lebih kuat dan akurat.   Kata Kunci: Keterampilan Konseling; Kesehatan Mental; Konselor Sebaya; Mahasiswa.